Kebijakan Moneter (BI Rate) dalam Pengendalian Harga (Inflasi) - Sudarjah, Gugum Mukdas; Yusuf, H. Anwar (Jurnal Trikonomika, 2008)
Inflation targeting (IT) as a framework for monetary policy has spread rapidly to developing countries since the 1990âs. At the first time, inflation targeting framework used base money (Mo) as the main intermediate target for reducing and sustaining inflation at low single digit. The management of the monetary base has also resulted in excessive volatility in short-term interest rates. Bank Indonesia as a monetary authority has changed the operational target from base money to BI rate. BI Rate become references of interest rate and has been transmission in single source rate at intercall bank money market (PUAB). Finally, PUAB influence interest rates, the level of credit and money supply through the money multiplier process, and ultimately the price level. This study aimed to obtain empirical evidence concerning the influence of BI Rate to inflation rate both in short term and long term.This research used Error Correction Model (ECM) include secondary data from July 2005 to December 2007. The result of research is BI Rate and PUAB Rate have influence in a significant manner on short term while import price of crude oil have influence in a significant manner on short and long term. Based on that result, we concluded that inflation rate in Indonesia influenced by cost-push inflation and demand-pull inflation can be controlled by central bank with BI Rate as the main intermediate target.